Women's Studies in Focus. Feminist Challenges to Knowledge - Eichler, Margrit; Luxton, Meg (Atlantis, 2006)
This contribution explores some of the issues that led to the development of Women's Studies in Canada in the 1970s. It offers a report of a workshop on this topic and presents two of the eighteen minipapers that participants wrote for the workshop.